Respon Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) terhadap Beberapa Bahan Aktif Herbisida pada Masa Peremajaan - Toto Suryanto (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Replanting was needed for unproductive of the old palm oil plants and having production under 13/ton/ ha. Replanting aims to change the oldest plants to increase the production. Replanting could be done with chemical, mechanical, and manual methodes. This research aims to get the best alternative of replanting by using some type of herbicide active ingredients and to get the right kind of active material for replanting of oil palm plants. This research was conducted at Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi on October, 2016 to May, 2017. The experiment was arranged in a descriptive method with five treatments of herbicide active materials: Paraquat dichlorida (A1), Trishlophyr (A2), 2,4-Dimetil amina (A3), Glifosat (A4) and Metil metsulfuron (A5). The dose of herbicide was 200/ ml/plant. Each treatments were two replications, so the total unit of experiments were 10 plants. The result showed that the treatments of herbicide with activated materials Paraquat dichloride, Trichlopyr, 2,4-Dimetil amina, Glifosat, and Metil metsulfuron with dose of 200 ml/plant as an effective chemical method in oil palm replanting and the most effective type of active ingredient was glyphosate.